Factors Associated With Persistent Urinary Incontinence Among Women Undergoing Female Genital Fistula Surgery in the Democratic Republic of Congo From 2017 to 2019 - Nembunzu, Dolores; Mayemba, Naomie; Sidibé, Sidikiba; Grovogui, Fassou Mathias; Aussak, Brian Tena Tena; Banze Kyongolwa, Don Félicien; Camara, Bienvenu Salim; Tripathi, Vandana; Delamou, Alexandre (Frontiers in Global Women's Health, 2022)
Background Despite high closure rates, residual urinary incontinence remains a common problem after successful closure of a vesico-vaginal fistula. The objective of this study was to identify factors associated with residual urinary incontinence in women with successful fistula closure in sites supported by the Fistula Care Plus project in the Democratic Republic of Congo (DRC). Material and Methods This was a retrospective cohort study using routine data extracted from the medical records of women undergoing fistula surgery in three hospitals supported by the Fistula Care Plus project in DRC between 2017 and 2019. We analyzed factors associated with residual urinary incontinence among a subsample of women with closed fistula at discharge. We collected data on sociodemographic, clinical, gynecological-obstetrical characteristics, and case management. Univariate and multivariate analyses were performed to determine the factors associated with residual urinary incontinence. Results Overall, 31 of 718 women discharged with closed fistula after repair (4.3%; 95% CI: 3.1–6.1) had residual incontinence. The leading causes identified in these women with residual incontinence were urethral voiding (6 women), short urethra (6 women), severe fibrosis (3 women) and micro-bladder (2 women). The prevalence of residual incontinence was higher among women who received repair at the Heal Africa (6.6%) and St Joseph's (3.7%) sites compared with the Panzi site (1.7%). Factors associated with increased odds of persistent urinary incontinence were the Heal Africa repair site (aOR: 54.18; 95% CI: 5.33–550.89), any previous surgeries (aOR: 3.17; 95% CI: 1.10–9.14) and vaginal surgical route (aOR: 6.78; 95% CI: 1.02–45.21). Conclusion Prior surgery and repair sites were the main predictors of residual incontinence after fistula closure. Early detection and management of urinary incontinence and further research to understand site contribution to persistent incontinence are needed.